Managing Media and Digital Organizations - Noam, Eli M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
What does it take for success in the media business? Creativity, innovation, and performance, of course. Plus experience and good judgment. However, it also requires an understanding of the principles and tools of management. This book summarizes the major dimensions of a business school curriculum and applies them to the entire media, media-tech, and digital sectors. Its chapters cover$1 (Bin a jargonless, non-technical way$1 (Bthe major management functions. First, creating a media product: the financing of projects and the management of technology, HR, production operations, intellectual assets, and government relations. Second, harvesting the product created: market research, marketing, pricing, and distribution. And third, is the control loop: media accounting and strategy planning. The book$1 (Bs interdisciplinary approach goes beyond an industry-by-industry coverage and centers around management functions. In the process, this book becomes an indispensable resource for those aiming for a career in the media and digital field, both in startups and established organizations. It is also a work that helps advance the entire field$1 (Bthe management of information resources and products$1 (Bto a more central role in business analysis. This book is designed to help those already in the sector or those joining it to become creative managers and managerial creatives. It aims to make managers in this field more knowledgeable, less blinded by hype, more effective, more productive, and more responsible. .s
I Overview -- 1. Introduction -- 2. The Information Environment -- II Production -- 3. Production Management in Media and Information -- 4. Technology Management in Media and Information Firms -- 5. Human Resource Management for Media and Information Firms -- 6. Financing Media, Information, and Communication -- 7. Intellectual Asset Management -- 8. Entertainment Law and Media Regulation -- 9. Demand and Market Analysis for Media and Information Products -- III Marketing -- 10. Marketing of Media and Information -- 11. Pricing of Media and Information -- 12. Distribution of Media and Information -- IV Feedback Loop -- 13. Accounting in Media and Information Firms -- 14. Strategy Planning in Media and Information Firms -- 15. Concluding Observations. .
Keywords: Communication; Industrial management; Culture; Technology; Management; Media and Communication; Media Management; Culture and Technology; Cultural Management; Management